Implementing English Morphological Awareness of Derivation in the Teaching of Vocabulary for Adult Learners - Astrit Maria (University of Muhammadiyah Prof. DR. HAMKA, 2019)
Vocabulary holds a significant role in language proficiency. When one’s vocabulary is limited, producing English both in written and oral form will hardly meet fluency. Morphological awareness reflects on greater improvement of both receptive and productive skills as it promotes vocabulary enrichment. Morphological awareness helps learners make sense of novel words as soon as they find the words. Besides, morphological exposure is recommended to begin since the very young age. However, expecting all young learners to equally receive proper education is too much. As a result, many adult learners remain puzzled of how to effectively improve their vocabulary that helps them perform English fluently. Therefore, this study aims to provide a set of lesson plan containing the appropriate teaching techniques that sufficiently facilitate adult learners to raise morphological awareness using derivations. Besides, it is to confirm that making adult learners to be proficient in language learning is possible. This study is a qualitative research employing participant observation in the form of video recording as the data elicitation technique. It is evident from the findings that there are nine techniques that adequately facilitate morphological awareness for adult language learners.